OPTIMALISASI KETERAMPILAN KOMUNIKASI PUBLIK SISWA SMA DI TENGAH DAMPAK DIGITALISASI - Surianto Surianto; Anis Hamidati (LPPM Institut Pendidikan Nusantara Global, 2026)
The use of social media among adolescents significantly affects students' communication patterns, especially in interpersonal and public communication. The frequency of gadget use has enabled students to communicate more easily via digital media than through face-to-face communication. Such a situation has consequences for students' self-confidence, formal communication, and their ability to serve as master of ceremonies, moderators, and news presenters. The purpose of this community service is to improve the public communication skills of 11 students at SMA Dharma Suci through public communication training. This training focused on improving students' capabilities as masters of ceremonies, moderators, and news presenters in schools. Some techniques used include interactive lecturing, public communication workshops, simulation, news reading, presentation individually or in groups, and discussion interactively. The program stage was divided into three phases: preparation, implementation, and evaluation by using pre-test, post-test, observation, and documentation techniques.